Interactions Between Immunomodulatory Biomaterials and Immune Microenvironment: Cues for Immunomodulation Strategies in Tissue Repair - Chen, Yi; Sun, Weiyan; Tang, Hai; Li, Yingze; Li, Chen; Wang, Long; Chen, Jiafei; Lin, Weikang; Li, Shenghui; Fan, Ziwen; Cheng, Yu; Chen, Chang (Frontiers in Bioengineering and Biotechnology, 2022)
The foreign body response (FBR) caused by biomaterials can essentially be understood as the interaction between the immune microenvironment and biomaterials, which has severely impeded the application of biomaterials in tissue repair. This concrete interaction occurs via cells and bioactive substances, such as proteins and nucleic acids. These cellular and molecular interactions provide important cues for determining which element to incorporate into immunomodulatory biomaterials (IMBs), and IMBs can thus be endowed with the ability to modulate the FBR and repair damaged tissue. In terms of cellular, IMBs are modified to modulate functions of immune cells, such as macrophages and mast cells. In terms of bioactive substances, proteins and nucleic acids are delivered to influence the immune microenvironment. Meanwhile, IMBs are designed with high affinity for spatial targets and the ability to self-adapt over time, which allows for more efficient and intelligent tissue repair. Hence, IMB may achieve the perfect functional integration in the host, representing a breakthrough in tissue repair and regeneration medicine.